Legal Implications of Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs No. 9 of 2006 on Freedom of Religion in the Perspective of Article 29 of the 1945 Constitution: Constitution Law - Putra, Irwan Sapta; Rochman, Arif; Karlina, Yunawati; Natan, Antonius (Jurnal Ilmiah Hukum dan Keadilan, 2025)
Legal implications of Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs No. 9 of 2006 on freedom of religion in the perspective of Article 29 of the 1945 Constitution. This regulation, which should guarantee freedom of religion, often becomes a tool of discrimination against religions such as Catholicism, Christianity, Hinduism, Buddhism, and Confucianism. This discrimination is exacerbated by the anarchic actions of radical groups and the absence of the government in enforcing the law, which results in unrest and arbitrariness by certain individuals. This journal highlights the importance of wise solutions to achieve harmony between religious communities and implement the mandate of the 1945 Constitution. By analyzing cases of discrimination and anarchic actions, it offers policy recommendations that can strengthen the protection of religious freedom and encourage the active role of the government in maintaining harmony between religious communities.